Ocean Literacy Competency : What Competencies Do Students Need Regarding Alignments with the Sea? - Juwintar Febriani Arwan; Mohammad Ali (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to map the ocean literacy competency needs through a competency needs assessment. The method used in this research is a survey. This research involved 116 respondents, namely junior high school teachers in the Riau Archipelago Province. The instrument used is an assessment of ocean literacy competency needs developed by researchers based on the results of a synthesis of several studies and the Blue Curriculum documentary by UNESCO. Data analysis technique used descriptive statistical analysis. Based on the research results, it was found that the average of the four ocean literacy competencies (building social-emotional; action for collective welfare; promoting sustainable development; and respecting each other), the teacher stated that they agreed if these competencies were infused in the subjects so that the achievement of ocean literacy could be achieved. This research is also an early stage in curriculum development, namely mapping competency requirements to be developed later in the next step. These competencies also can be integrated or infused into various subject competencies as curriculum and instruction innovation. Later, from the integration or infusion competencies, teachers can support students to have sympathy, awareness, caring, and responsible for the ocean and marine resources.